Peningkatan Literasi Narkotika dan Psikotropika melalui Edukasi dan Pembentukan Satgas Anti Narkoba di SMPN 1 Pacet Kabupaten Mojokerto - Kristianto, Sonny; Yudianto , Ahmad; Putri , Rury Eryna; Widodo , Wimbuh Tri; Ripki, Nadia; Zulqaida, Salma (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2024)
Drug abuse among adolescents continues to rise, particularly within school-aged groups. SMPN 1 Pacet in Mojokerto Regency, with students aged 13-15 years old, is an environment vulnerable to this risk. This community service activity aims to increase students' literacy about the dangers of narcotics and psychotropic drugs. This program involved 50 Grade 9 students along with the Osis/MPK and presented experts from Social Service and Airlangga University. Methods included a pre-test, education, practice of urine drug testing using rapid diagnostic tests independently and post-test. The results showed an increase in the average score of students' understanding by 12.4%, as well as the formation of the Anti-Drug Task Force as an agent of change. This success supports the goals of SDG 4 (quality education) and SDG 16 (peace, justice, and strong institutions). This program demonstrates the effectiveness of participatory-based education in creating a drug-free school environment.